Aprendizagem musical e manutenção de classes de estímulos equivalentes - Madeira, Igor Eduardo Coutinho (2012)
Stimulus equivalence paradigm has pointed to increasingly effective methods and economic teaching of music startup. Little research in Brazil have been carried out with the aim of verifying the formation and maintenance of equivalent classes between auditory, execution of instruments and reading musical notes. This study aimed to verify the training effect of equivalence between musical stimuli (musical notes/notes/drawings notes names) on the acquisition and maintenance of equivalence classes over time on tests of gift drawings of musical notes. For this, two experiments were carried out. The first experiment aimed to verify the adaptation of the methodology of equivalency of stimuli to the teaching of music in a computer system (APRM software) for the formation of classes of equivalent stimuli necessary to teaching of musical ability. Auditory, musical notes drawn into musical pentagram (B) and name the notes with symbols of ciphers (C) were used for programming tasks. Was elected participants 11 participants of the elementary and secondary public schools of Governador Valadares-MG. The participants were underwent pre-test initial baseline, to training of conditional relations AB and BC and the learning scan test, conducted from 2 to 5 days after the training phase. The results of the tests of symmetry and equivalence conducted within 2 to 5 days after the training of conditional relations AB and BC showed that ten participants managed to form equivalence classes and only three participants were able to meet the criteria for formation of equivalence classes. The second experiment aimed to verify the training effect of equivalence between musical stimuli (A-/B-auditory designs of musical notes/C-notes names with symbols of digits) on the maintenance of equivalence classes over time and tests recollections of drawings of musical notes. The participants were the same as those for Experiment 1 submitted to the procedure of choice according to the model, in the APRM, in five steps for the formation of seven equivalence classes with three stimuli each: Pd-initial baseline test, training of conditional relations AB and BC and maintenance Tests involving symmetry relations (BA, CA) and Equivalence (BC and CA) carried out in three distinct periods (2 to 5 days, 30 to 35 days and 60 to 80 days). The results showed that in tests conducted during the last maintenance period (60 to 80 days), eight participants agreed 100% free test tips and seven participants managed to hit all the test with hinting. Four participants managed to reach the 90% criterion of hits on the test of symmetry and all participants formed equivalence class after 60 to 80 days of training phase. The results of the two experiments suggest that the procedure matching-to-sample is efficient in the formation and maintenance of classes of equivalent musical learning-related stimuli and that new studies are performed in order to check the variables that interfere in the formation of symmetry using auditory stimuli.